Communication Barriers Between Malaysian Students And Arab Tourists - Abdul Azim Mohamad Isa; Fitri Nurul’ain Nordin; Ghazali Yusri Abd Rahman; Ibrahim Youssef Abdelhamid; Hazrati Yahaya; Siti Suhailah Abdul Rahman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
A communication barrier is anything that comes in the way of receiving and understanding messages that one sends to another to convey his ideas, thoughts, or any other kind of information. These various barriers of communication block or interfere with the message that someone is trying to send. This paper aims to identify communication barriers occurring during interview sessions conducted by students with Arab tourists, and to analyze the situation that led to the communication barrier. Based on Effendy (2009) and Rani (2016), the research divided the communication barriers into four categories: cultural barrier, language barrier, environmental barrier, and attitude barrier. This paper applies a qualitative method, which its instrument is content analysis by analyzing 20 interview videos to study the communication barriers happening among the students and the Arab tourists. The research analysis instrument used is document analysis based on the checklist made for identifying the communication barriers. The researcher observed each scene to identify communication barriers that happened between them, while document analysis was applied to analyze the situation that triggered the communication barriers. Language barrier is the most recorded barrier for 87 times, with the lack of vocabulary found as the main issue among the students while conducting the interview with the Arab tourist.